Psychometric properties and validation of the metacognitive self-assessment scale (MSAS) in a Turkish sample - Yilmazer, Eda; Hamamci, Zeynep; Tuerk, Fulya (FRONTIERS MEDIA SA, 2024)
Objective: Metacognition, a multifaceted psychological construct, encompasses recognising and explaining one's cognitive processes and those of others. Notably, deficits in metacognitive abilities are linked with diminished social performance, reduced quality of life, and increased severity of Personality Disorders (PD). While there are other assessment tools available in Turkish for evaluating metacognition, none offer the same combination of speed, simplicity, flexibility, and multidimensionality for screening metacognitive abilities as the Metacognition Self-Assessment Scale (MSAS).The Metacognitive Self-Assessment Scale (MSAS) was designed to evaluate various metacognitive functions-namely, Monitoring, Integration, Differentiation, and Disintegration-as described by the Metacognitive Multifunction Model. This study aims to translate and validate the MSAS for Turkish culture. Method: To check the factor structure's suitability for the Turkish population, 467 non-clinical participants (67.7% female, ranged from 18 to 31, mean 24.18; 3.25) were included. Results: Initial analyses confirm that the scale is a valid and dependable instrument for Turkish culture. Construct validity, represented by the 18 items and four subscales, was confirmed through Confirmatory Factor Analysis (CFA) and criterion validity assessments. As well as the test-retest reliability of the scale was confirmed. Based on these findings, it was concluded that the scale is valid and reliable for use in Turkey. The model aligns well with empirical data, highlighting its strong construct validity and indicating good reliability of the scale. Conclusion: The Turkish version of the MSAS, developed to measure metacognition and its associated components, has proven to be a credible and reliable tool, especially in non-clinical settings.
Keywords: metacognition; assessment; reliability; validity; scale; OBSESSIVE-COMPULSIVE SYMPTOMS; THOUGHT CONTROL QUESTIONNAIRE; PERSONALITY-DISORDERS; FIT INDEXES; R PACKAGE; PSYCHOTHERAPY; MIND; COGNITION; THINKING; WORRY; Psychology